SAT0401 Towards a Multidimensional Patient Reported Outcome Measures Assessment: Development and Validation of a Questionnaire for Patients with Fibromyalgia. (23rd January 2014) - El Miedany, Y.; El Gaafary, M.; Youssef, S.; El Aroussy, N.; Ahmed, I.; Palmer, D.
Abstract : Background: Rheumatology is embarking on a fundamental redesign of rheumatic disease care. It became mandatory not only to recognize disease activity core set data, but also the risks for other co-morbidities associated with the disease. Measurement of patient reported outcomes have become critical in both standard clinical practice and long term observational studies. Objectives: To assess the validity, reliability and responsiveness to change of a patient self-reported questionnaire that can assess construct outcome measures of patients with fibromyalgia. Methods: The PROMs was conceptualized based on frameworks used by the WHO Quality of Life tool, as well as the PRO measurement information system (PROMIS). Cognitive interviews were conducted with 47 fibromyalgia patients (diagnosed according to ACR criteria), with a range of severity to identify item pool of questions. Item selection and reduction was achieved based on patients as well as an interdisciplinary group of physicians, nurses, and health educators, in addition to clinometric and psychometric methods. The latter included Rasch and internal consistency reliability analyses. The questionnaire includes assessment of functional disability, quality of life, VAS (0-100) for sleep disturbance, waking feeling unrefreshed, global status, fatigue, body pain and impact of mood changes, in addition to review of the systems, falls and cardiovascular risks, self-helplessness as well as self-reported soft tissue painful areas. In addition, every patient completed SF-36 and Euro QoL 5D questionnaires. Results: The PROMs questionnaire was reliable as demonstrated by a high-standardized alpha (0.893-0.967). Patient reported tender spots correlated significantly with the physician's scores (r= 0.818). Content construct assessment of the PROMs-functional disability and QoL revealed significant correlation (P< 0.01) with both SF-36 and Euro QoL scores. Changes in functional disability, quality of life as well as self-helplessness scores showed significant (P< 0.01) variation with diseases activity status and response to therapy. Mean time to complete the questionnaire was 7.04 ± 0.92 min. The PROMs questionnaire showed also a high degree of comprehensibility (9.5). Conclusions: The developed PROMs questionnaire is a reliable and valid instrument for assessment of patients suffering from fibromyalgia. Being short, rapid and comprehensive, this adds more to its applicability. The data support the value of completion of the simple 2 pages patient questionnaire, which provides a quantitative written documented record by the patient, at each visit to the clinic. Disclosure of Interest: None Declared